MEMBENTUK JIWA ENTREPRENEUR BERKARAKTER INOVATIF DAN KREATIF - Lestari Nasution, Winda Suci; Nusa, Patriot (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Entrepreneurship is an activity that is consistently carried out to turn ideas into profitable business activities. Profitable business activities can be realized well if everyone can first cultivate an entrepreneurial spirit. Entrepreneurship spirit itself has several characteristics, including forming an entrepreneurial spirit with an innovative and creative character so that the dream of becoming a successful entrepreneur will come true. In Indonesia very minimal employment has resulted in low employment, coupled with the Covid-19 pandemic which has disrupted the economy and workforce, thereby increasing the unemployment rate due to a large wave of layoffs. Entrepreneurship based on a creative and innovative attitude is expected to be one of the solutions in reducing unemployment because entrepreneurship based on a creative and innovative attitude will survive and thrive in difficult economic conditions. This activity is carried out online. The purpose of this activity is to take steps to realize entrepreneurship based on a creative and innovative attitude by sharing knowledge related to the formation of an entrepreneurial spirit with a creative and innovative character, facilitating and educating to commit to doing business until it succeeds.